2023
DOI: 10.3389/frph.2023.1143579
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid is associated with favourable hormonal profiles among infertile males

Abstract: IntroductionInfertility affects about 16% of North American couples, with the male factor contributing to ∼30% of cases. Reproductive hormones play an integral role in regulating the reproductive system and consequently, fertility. Oxidative stress reduces testosterone synthesis, and reduction in oxidative stress can improve hormone profiles. Ascorbic acid is a potent antioxidant that accounts for up to 65% of seminal antioxidant activity; however, its effects on reproductive hormones in humans are unknown.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…No studies have examined these associations in men with infertility. A recent study looking at ascorbic acid (vitamin C), a micronutrient that facilitates iron absorption, found that ascorbic acid was associated with favorable hormonal profiles in infertile males [ 49 ]. Ascorbic acid was inversely associated with LH and age-dependently positively associated with TT [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…No studies have examined these associations in men with infertility. A recent study looking at ascorbic acid (vitamin C), a micronutrient that facilitates iron absorption, found that ascorbic acid was associated with favorable hormonal profiles in infertile males [ 49 ]. Ascorbic acid was inversely associated with LH and age-dependently positively associated with TT [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies which have noted the influence of sex hormones on vitamin C concentrations have relied on cellular and animal models 68 . One recent cross-sectional study in infertile men found there was an inverse association between serum ascorbic acid and luteinizing hormone levels, however, the relationship between vitamin C and sex hormones in humans needs to be further explored 9 .…”
Section: Introductionmentioning
confidence: 99%